2016
DOI: 10.1007/s40279-016-0618-6
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Contact Sports and Colonization with Staphylococcus aureus in a Prospective Cohort of Collegiate Athletes

Abstract: Objective Athletes have higher risk of infection with Staphylococcus aureus than the general population. Most studies in athletes have included primarily male contact sports participants and have not assessed S. aureus carriage over time. We aimed to examine the epidemiology and risk factors of S. aureus carriage in a cohort of male and female collegiate athletes. Study Design We conducted a prospective cohort study of 377 varsity collegiate athletes from August 2008 to April 2010. A baseline questionnaire a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 32 publications
0
10
1
Order By: Relevance
“…10,16 This is further evidenced by the fact that other studies demonstrated that athletes in contact sports become more frequently colonized with S aureus than do participants in noncontact sports. 14,20 Krutsch et al reported additional potential explanations, including differences in colonization of skin bacteria owing to differences in temperature and excretion of sweat depending on participation in different sports. Further study is required to better understand these complex factors.…”
Section: Discussionmentioning
confidence: 99%
“…10,16 This is further evidenced by the fact that other studies demonstrated that athletes in contact sports become more frequently colonized with S aureus than do participants in noncontact sports. 14,20 Krutsch et al reported additional potential explanations, including differences in colonization of skin bacteria owing to differences in temperature and excretion of sweat depending on participation in different sports. Further study is required to better understand these complex factors.…”
Section: Discussionmentioning
confidence: 99%
“…Although this microbe persists in soil [33], leptospirosis is mainly a concern for events with open water swimming, including triathlons [34, 35], where it is difficult to know whether the mud or water is the source. We note that while Staphylococcus aureus has been documented as a transmission risk in contact sports [36], it does not appear to have been documented in the literature as being a cause of sports-related mud-borne infection outbreaks.…”
Section: Introductionmentioning
confidence: 89%
“…This increase is not due to the appearance and development of repeated outbreaks, and only one outbreak or one infected athlete is enough to increase the spread and the percentage of individuals infected, thanks to SA's ability to escape from common antibiotic therapies. Another important study on the appearance and spread of SA was conducted by Jiménez-Truque and co-authors [25]. They subjected 377 athletes to a nasal swab, both at the time of enrolment within the study and every month, in order to monitor the state of health and the presence of SA or the appearance of MRSA.…”
Section: Importance Of Fomites In S Aureus Infection Outbreaksmentioning
confidence: 99%